Characterization of Naturally Acquired Immunity to a Panel of Antigens Expressed in Mature P. falciparum Gametocytes - Muthui, Michelle K.; Takashima, Eizo; Omondi, Brian R.; Kinya, Christine; Muasya, William I.; Nagaoka, Hikaru; Mwai, Kennedy W.; Orindi, Benedict; Wambua, Juliana; Bousema, Teun; Drakeley, Chris; Blagborough, Andrew M.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction Naturally acquired immune responses against antigens expressed on the surface of mature gametocytes develop in individuals living in malaria-endemic areas. Evidence suggests that such anti-gametocyte immunity can block the development of the parasite in the mosquito, thus playing a role in interrupting transmission. A better comprehension of naturally acquired immunity to these gametocyte antigens can aid the development of transmission-blocking vaccines and improve our understanding of the human infectious reservoir. Methods Antigens expressed on the surface of mature gametocytes that had not previously been widely studied for evidence of naturally acquired immunity were identified for protein expression alongside Pfs230-C using either the mammalian HEK293E or the wheat germ cell-free expression systems. Where there was sequence variation in the candidate antigens (3D7 vs a clinical isolate PfKE04), both variants were expressed. ELISA was used to assess antibody responses against these antigens, as well as against crude stage V gametocyte extract (GE) and AMA1 using archived plasma samples from individuals recruited to participate in malaria cohort studies. We analyzed antibody levels (estimated from optical density units using a standardized ELISA) and seroprevalence (defined as antibody levels greater than three standard deviations above the mean levels of a pool of malaria naïve sera). We described the dynamics of antibody responses to these antigens by identifying factors predictive of antibody levels using linear regression models. Results Of the 25 antigens selected, seven antigens were produced successfully as recombinant proteins, with one variant antigen, giving a total of eight proteins for evaluation. Antibodies to the candidate antigens were detectable in the study population (N = 216), with seroprevalence ranging from 37.0% (95% CI: 30.6%, 43.9%) for PSOP1 to 77.8% (95% CI: 71.6%, 83.1%) for G377 (3D7 variant). Responses to AMA1 and GE were more prevalent than those to the gametocyte proteins at 87.9% (95% CI: 82.8%, 91.9%) and 88.3% (95% CI: 83.1%, 92.4%), respectively. Additionally, both antibody levels and breadth of antibody responses were associated with age and concurrent parasitaemia. Conclusion Age and concurrent parasitaemia remain important determinants of naturally acquired immunity to gametocyte antigens. Furthermore, we identify novel candidates for transmission-blocking activity evaluation.